Role of proper postnatal care in continued exclusive breastfeeding among young Indonesian mothers - Wahyu Triadmajani; Shinta Prawitasari; Abdul Wahab (Clinical and Experimental Pediatrics)
Background Exclusive breastfeeding (EBF) provides numerous health benefits to children. However, the EBF rate is unsatisfactory among young mothers because they often experience difficulties. Thus, interventions during the postnatal period are imperative to encouraging EBF practices in these populations. Postnatal care (PNC) should be delivered appropriately to ensure a positive postnatal experience; however, there has been little discussion of evidence therein to date. Purpose This study investigated the association between proper PNC and EBF practices among young Indonesian mothers. Methods This cross-sectional study analyzed data from the 2017 Indonesia Demographic Health Survey. All mothers aged 15–24 years who delivered an infant within the 2 years preceding the survey were included. Mothers were considered to be receiving proper PNC if they started breastfeeding soon after delivery, attended a PNC appointment within 2 days after giving birth, and received breastfeeding counseling and observation during the PNC visit. Results Approximately 51.6% of infants under 6 months of age born to young mothers (those aged 15–24 years) were exclusively breastfed. Appropriate PNC was received by approximately 24.3% of the total population. The correlation between proper PNC and EBF practices was significant among adolescent mothers aged 15–19 years after an age stratification analysis (odds ratio, 8.22; 95% confidence interval, 1.957–34.524). Maternal age became a noticeable confounder after a risk-stratification analysis. Conclusion Our findings imply the importance of breastfeeding service delivery during the early postnatal period in continuing EBF. Ensuring high PNC quality helps ensure positive postnatal experiences, particularly for adolescent mothers.